Effect of Tomato Pomace Extracts on the Shelf‐Life of Modified Atmosphere‐Packaged Lamb Meat. Issue 4 (27th June 2016) - Andres, A.I.; Petron, M.J.; Delgado‐Adamez, J.; Lopez, M.; Timon, M.
Abstract: Tomato production is one of the main industries in Spain and a large amount of by‐products, tomato pomace (TP) is generated every year. TP is a promising source of compounds with nutritional, antioxidant and antimicrobial potential. The aim of this work was to study the in vitro antioxidant potential of extracts obtained from TP by using either ethyl acetate (EA) or ethanol (E) solvents, and to evaluate the effect of the addition of extracts by spreading on lamb longissimus thoracis surface in order to improve shelf‐life. EA and E extracts showed a similar in vitro antioxidant activity which is in good relation with similar lycopene, phenol and β‐carotene contents found in those extracts. Redness ( a *) decrease during storage was less intense in meat longissimus thoracis with added extracts ( P < 0.05) than in meat without added extracts. The addition of EA and E extracts did not significantly affect TBARs and free thiol content ( P > 0.05) in meat stored during 7 days. Microbial counts were not either affected ( P > 0.05). Practical Appliactions: This manuscript deals with the antioxidant and antimicrobial potential of tomato pomace by‐products and specifically, their extracts. Tomato concentrate by‐products are produced in a great amount, and most of them are underused as animal feed. The value of these by‐products could be increased as used as potential antimicrobial and/or antioxidant agents in foods. A number of works have applied different parts of tomato by‐products, such as the seed, the peel, or both, in certain food products. However, as far as we are concerned there is no scientific literature dealing with obtaining extracts from tomato pomace and adding them to meat or meat products. In this research we obtained the extracts by solvent extraction, studied their composition and in vitro potential and added them to meat in order to extend its shelf‐life.